Literature Review for Iliaca, Scapula, and Fibula Free Flap as A Modality in Mandibular Ameloblastoma Reconstruction - Tillasman, Natassya Sandra; Laksmi, Putu Pradnyasanti; Roosseno, Ratna Rayeni Natasha; Hamid, Agus Roy Rusly Hariantana (CoinReads Media Prima, 2024)
Introduction: Mandibular reconstruction is complex as there are multiple goals for the final outcome, with a main focus of returning form and function as close to baseline as possible. It may be challenging for ameloblastoma treatment which is focused on surgical resection with a wide margin of normal tissue because of its high propensity for regional invasion. Free vascularized bone flaps are widely recognized as the optimal reconstruction for this case and have been widely developed from the iliaca, scapula, or fibula. Methods: Using the PubMed and Google Scholar databases, we searched for reported cases of ameloblastoma published in the English-language literature. Results: We were able to retrieve 47 acceptable literatures and perform a comprehensive literature review, particularly those using microvascular composite free flaps, then compared iliaca, scapula, and fibula free flaps to identify optimal flap choice for mandibular reconstruction. In addition, we present an additional case of ameloblastoma affecting the anterior mandible in a 26-year-old male patient. Conclusion: Microsurgical techniques are now considered safe and reliable in reconstruction of the jaws by reestablishing the continuity and normal anatomy, aiding to restore the normal function of swallowing, mastication, and speech production. In our experience, free osteocutaneous fibula flap technique is a further confirmation of its potential in the reconstruction of hard and soft tissue in maxillofacial surgery.